2007
DOI: 10.1111/j.1442-200x.2007.02443.x
|View full text |Cite
|
Sign up to set email alerts
|

13C‐phenylalanine breath test correlates with liver fibrosis in postoperative biliary atresia

Abstract: The PBT values correlated well with liver fibrosis in postoperative BA children. Because PBT is a non-invasive approach, results from this method may serve as a useful and reliable index for post-surgical monitoring of children operated on for liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Given that, as yet, few studies have been performed involving small groups of children with rare diseases, 178–181 the use of 13 C‐LFBT for clinical purposes cannot be recommended in the pediatric population, so far.…”
Section: C‐liver Function Breath Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that, as yet, few studies have been performed involving small groups of children with rare diseases, 178–181 the use of 13 C‐LFBT for clinical purposes cannot be recommended in the pediatric population, so far.…”
Section: C‐liver Function Breath Testsmentioning
confidence: 99%
“…For instance, the effect of transarterial chemoembolization on liver function has been monitored by 13 C-methacetin test, 174 and several studies suggest that this test could also be used for planning of hepatic resections. [175][176][177] Given that, as yet, few studies have been performed involving small groups of children with rare diseases, [178][179][180][181] the use of 13 As discussed before, potential confounders of test results detailed in general methodology have to be avoided. For 13 C-LFBT that investigate cytochrome P 450 enzymes, drugs with potential influence on cytochrome P 450 metabolism are of particular relevance, [182][183][184] and it may be necessary to perform a test despite ongoing medication.…”
Section: Recommendation 43 Adult Patients Adolescents and Older Childrenmentioning
confidence: 99%
“…The metabolite 3-(2-Hydroxyphenyl) propionic acid was significantly negatively correlated with HF-related indices and positively correlated with TJPs, and it was involved in phenylalanine metabolism. A study reported that in children with HF after biliary atresia, significantly decreased phenylalanine metabolism is detected by the (13) C-phenylalanine breath test ( Wada et al, 2007 ). The metabolite 5-L-Glutamyl-taurineis, an intermediate in Taurine and hypotaurine metabolism, was significantly and positively correlated with all HF-related indices.…”
Section: Discussionmentioning
confidence: 99%